Bridge-Crane Hoist Mass Angular Oscillation - Ly, Hung; Chau, Than; Nguyen, Huong (The Indonesian Institute of Science and Technology Research, 2025)
The oscillation of hoisting masses in bridge cranes significantly impacts system stability, resulting in adverse effects such as excessive dynamic loads, inaccurate positioning during loading and unloading, and overall instability. Therefore, the angular oscillation of the hoisting mass must be controlled in the design of bridge cranes. This paper presents a mathematical model for the analysis of the angular oscillation of a hoisting load, both during oscillation and trolley movement. The MATLAB/Simulink software was used to simulate the dynamic behavior of the model to gain insights into the oscillation angle and its limitations. The results substantiate the reliability of the proposed model for predicting the angular oscillation of hoisting loads in bridge cranes.